Nourishing a Partnership to Improve Middle School Lunch Options. Issue 1 (January 2015) - Reich, Stephanie M.; Kay, Joseph S.; Lin, Grace C.
<x xml:space="preserve">Abstract</x> Community-based participatory research is predicated on building partnerships that tackle important issues to the community and effectively improve these issues. Community-based participatory research can also be an empowering experience, especially for children. This article describes a university-community partnership in which students at a low-income middle school worked to improve the quality of the cafeteria food provided to the 986 students eligible for free and reduced price lunches. The project led to menu changes, improved communication between youth, school administrators, and district staff, and enabled youth to enact school improvements that were beneficial for their health.